HyperSlides: Dynamic Presentation Prototyping - Edge, Darren; Savage, Joan M.; Yatani, Koji (CHI 2013 Conference on Human Factors in Information Systems, 2013)
Presentations are a crucial form of modern communication, yet there is a dissonance between everyday practices with presentation tools and best practices from the presentation literature. We conducted a grounded theory study to gain a better understanding of the activity of presenting, discovering the potential for a more dynamic, automated, and story-centered approach to prototyping slide presentations that are themselves dynamic in their ability to help presenters rehearse and deliver their story. Our prototype tool for dynamic presentation prototyping, which we call HyperSlides, uses a simple markup language for the creation of hierarchically structured scenes, which are algorithmically transformed into hyperlinked slides of a consistent and minimalist style. Our evaluation suggests that HyperSlides helps idea organization, saves authoring time, creates aesthetic layouts, and supports more flexible rehearsal and delivery than linear slides, at the expense of reduced layout control and increased navigation demands.